2021
DOI: 10.1111/mmi.14786
|View full text |Cite
|
Sign up to set email alerts
|

The zinc finger protein StMR1 affects the pathogenicity and melanin synthesis of Setosphaeria turcica and directly regulates the expression of DHN melanin synthesis pathway genes

Abstract: The heterothallic ascomycete Setosphaeria turcica (anamorph Exserohilum turcicum) is a fungal pathogen of corn (Zea mays) and causal agent of northern corn leaf blight (NCLB). NCLB has spread worldwide, especially in northern China, and is one of the most important corn diseases (Abera et al., 2016;Dong et al., 2008). The emergence of NCLB before anthesis in corn may result in significant yield losses of susceptible varieties. The occurrence of NCLB depends on the successful invasion of pathogenic fungi. Upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The Zn 2 Cys 6 zinc cluster proteins are a family of transcription factors found exclusively in fungi [ 33 ]. They function as transcriptional regulators and are involved in a wide variety of biological processes, including asexual and sexual development, secondary metabolite biosynthesis, carbon and nitrogen metabolism, stress responses, pleiotropic drug resistance, and fungal pathogenesis [ 34 , 35 , 36 , 37 , 38 ]. However, the functions of Zn 2 Cys 6 TFs in different fungi are diverse.…”
Section: Discussionmentioning
confidence: 99%
“…The Zn 2 Cys 6 zinc cluster proteins are a family of transcription factors found exclusively in fungi [ 33 ]. They function as transcriptional regulators and are involved in a wide variety of biological processes, including asexual and sexual development, secondary metabolite biosynthesis, carbon and nitrogen metabolism, stress responses, pleiotropic drug resistance, and fungal pathogenesis [ 34 , 35 , 36 , 37 , 38 ]. However, the functions of Zn 2 Cys 6 TFs in different fungi are diverse.…”
Section: Discussionmentioning
confidence: 99%
“…For the RNAseq analysis, differentially expressed genes (DEGs, in Additional file 1 : Table S4) from three biological replicates of the mutant and WT were identified by Deseq R with a false discovery rate of 1% (fold-change ≥ 2.0, P < 0.01). The DEGs were analyzed using Gene Ontology (GO) analysis in the GO-seq package and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis [ 96 , 97 ] using the KEGG Orthology (KO)-Based Annotation System (KOBAS) to explore their biological roles based on the classification system including plasma membrane, cell periphery, regulation of cellular process, cellular component organization, regulation of biological process, oxidation-reduction process, oxidoreductase activity, and melanin biosynthesis. The threshold for the significant enrichment of GO terms was P <0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Cmr1 is characterized by the presence of two types of DNA binding motifs, two Cys 2 His 2 zinc finger motifs and one GAL4-like Zn(II) 2 Cys 6 binuclear cluster DNA-binding motif. Until now, Cmr1 homologs that have been identified and confirmed their roles as the regulators in the DHN-melanin biosynthesis pathway of several plant fungal pathogens, include Pig1 in Magnaporthe grisea (Tsuji et al 2000 ), Cmr1 in Cochliobolus heterostrophus (Eliahu et al 2007 ), Bmr1 in Bipolaris oryzae (Kihara et al 2008 ), Amr1 in Alternaria brassicicola (Cho et al 2012 ), CmrA in Alternaria alternata (Fetzner et al 2014 ), BcSMR1 in Botrytis cinerea (Zhou et al 2017 ), Zmr1 in Zymoseptoria tritici (Krishnan et al 2018 ), CgCmr1 in Colletotrichum gloeosporioides (Wang et al 2021a , b ), and StMR1 in Setosphaeria turcica (Zhang et al 2022 ). Apart from a role in controlling DHN-melanin biosynthesis, Cmr1 homologs also affect the morphology and pathogenicity of some phytopathogenic fungi, suggesting the functional diversification of Cmr1 homologs.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, two Cmr1 homologs including Amr1 in A. brassicicola (Cho et al 2012 ) and CmrA in A. alternata (Fetzner et al 2014 ) have been identified and characterized in Alternaria . The function of Cmr1 homologs in regulating the DHN-melanin biosynthesis is highly conserved in A. brassicicola , A. alternata , and other fungi described above (Tsuji et al 2000 ; Eliahu et al 2007 ; Kihara et al 2008 ; Cho et al 2012 ; Fetzner et al 2014 ; Zhou et al 2017 ; Krishnan et al 2018 ; Wang et al 2021a , b ; Zhang et al 2022 ). Interestingly, based on the amino acid sequence comparison between Amr1 and CmrA, there was one amino acid insertion at site 934 in Amr1 and 31 polymorphic sites (data not shown), suggesting that the amino acid sequences have diverged in Amr1 and CmrA.…”
Section: Introductionmentioning
confidence: 99%